2006
DOI: 10.1146/annurev.ento.51.110104.151136
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Significance of Tallgrass Prairie Arthropods

Abstract: Tallgrass prairie (TGP) arthropods are diverse and abundant, yet they remain poorly documented and there is still much to be learned regarding their ecological roles. Fire and grazing interact in complex ways in TGP, resulting in a shifting mosaic of resource quantity and quality for primary consumers. Accordingly, the impacts of arthropod herbivores and detritivores are expected to vary spatially and temporally. Herbivores generally do not control primary production. Rather, groups such as grasshoppers have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 137 publications
(163 reference statements)
0
64
0
Order By: Relevance
“…Paralleling community-level responses, we found that herbivore biomass was enhanced in more diverse and forest-dominated landscapes. Herbivores are not known to directly control grass biomass in prairie systems but may control forb biomass and have important indirect effects [49], such as increasing litter quality and decomposition [50], contributing nutrients [51], and changing the throughfall chemistry [52] and energy demands [53] of damaged plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Paralleling community-level responses, we found that herbivore biomass was enhanced in more diverse and forest-dominated landscapes. Herbivores are not known to directly control grass biomass in prairie systems but may control forb biomass and have important indirect effects [49], such as increasing litter quality and decomposition [50], contributing nutrients [51], and changing the throughfall chemistry [52] and energy demands [53] of damaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the role of predatory and parasitic arthropods in prairies have revealed a variety of controls on herbivorous arthropod populations through lethal and nonlethal effects that alter individual fitness and behavior [21,49]. By affecting herbivorous arthropod populations, predatory arthropods can also increase primary production through top-down trophic cascades [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…they can represent the bulk of the overall invertebrate biomass in the grass layer (gangwere et al 1997, Jamison et al 2002, whiles & Charlton 2006, readily responding to changes in habitat quantity (baldi & kisbenedek 1999) and traditional grazing activities (batáry et al 2007, sorino et al 2009, weiss et al 2013). furthermore, they represent the main food resource for many other taxa, including endangered species of birds, reptiles and mammals (e.g.…”
Section: Introductionmentioning
confidence: 99%